GTAC enables parallel genotyping of multiple genomic loci with chromatin accessibility profiling in single cells - Turkalj, Sven; Jakobsen, Niels Asger; Groom, Angus; Metzner, Marlen; Riva, Simone G; Gür, E Ravza; Usukhbayar, Batchimeg; Salazar, Mirian Angulo; Hentges, Lance D; Mickute, Gerda; Clark, Kevin; Sopp, Paul; et al. (Cell stem cell, 2023)
Understanding clonal evolution and cancer development requires experimental approaches for characterizing the consequences of somatic mutations on gene regulation. However, no methods currently exist that efficiently link high-content chromatin accessibility with high-confidence genotyping in single cells. To address this, we developed Genotyping with the Assay for Transposase-Accessible Chromatin (GTAC), enabling accurate mutation detection at multiple amplified loci, coupled with robust chromatin accessibility readout. We applied GTAC to primary acute myeloid leukemia, obtaining high-quality chromatin accessibility profiles and clonal identities for multiple mutations in 88% of cells. We traced chromatin variation throughout clonal evolution, showing the restriction of different clones to distinct differentiation stages. Furthermore, we identified switches in transcription factor motif accessibility associated with a specific combination of driver mutations, which biased transformed progenitors toward a leukemia stem cell-like chromatin state. GTAC is a powerful tool to study clonal heterogeneity across a wide spectrum of pre-malignant and neoplastic conditions.